The Influence of Patuli Media (Literacy Adventure Board) on the Early Reading Ability of Elementary School Students - Nurul Dinda Aulia; Nurdiana Siregar (BASICA, 2026)
Initial reading skills are basic skills that are important for elementary school students to master. However, some low-grade students still have difficulty recognizing letters, reading syllables, matching words to pictures, and reading simple sentences. These problems are influenced by the underuse of engaging and interactive learning media in the learning process. This study aims to determine the influence of Patuli media (Literacy Adventure Board) on the initial reading ability of elementary school students. This study uses a quantitative approach with quasi-experimental methods and a nonequivalent control group design. The research sample consisted of 36 grade II students from SD Negeri 105447 Nagori, who were divided into experimental and control classes. Data collection techniques include pretest and posttest tests, observation, and documentation. Data analysis was carried out using descriptive statistics, normality tests, homogeneity tests, N-Gain tests, and independent t-tests.  The results showed that the average posttest score of the experimental class was higher than that of the control class, namely 34.17 and 23.83. The results of the hypothesis test showed a p-value of 0.000 < 0.05, so H0 was rejected, and Ha was accepted. Thus, Patuli media has proven to be effective in improving initial reading skills."That